Manajemen Santri dalam Penguatan Spirit Entrepreneur di Ponpes Al-Ihya Ulumaddin 2 Kebonbaru Cilacap - Imam Satibi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2020)
The purpose of this study is to analyze the management of strengthening the entrepreneurial spirit at Al-Ihya Ulumaddin Islamic Boarding School 2 Kebonbaru Cilacap Selatan. The research approach used is qualitative. Researchers collected data by way of observation, interviews, and documentation studies. Furthermore, the data were analyzed using an interactive model in the form of data recording, data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that: (1) Planning for Strengthening Entrepreneurial Spirit at Islamic Boarding School Al-Ihya Ulumaddin 2 Kebonbaru Cilacap Selatan; (2) Organizing Strengthening Entrepreneurial Spirit at the Al-Ihya Ulumaddin Islamic Boarding School 2 Kebonbaru Cilacap Selatan is carried out by dividing personnel tasks along with their job descriptions; (3) Guidance on Strengthening Entrepreneurial Spirit at Al-Ihya Ulumaddin Islamic Boarding School 2 Kebonbaru Cilacap Selatan is divided into three forms, namely theoretical implementation, practical implementation and incidental implementation; and (4) Supervision of Directions for Strengthening Entrepreneurial Spirit at AlIhya Ulumaddin Islamic Boarding School 2 Kebonbaru Cilacap Selatan is carried out by determining program implementation standards, program assessments, and program implementation improvements/solutions.